Correlation between hematological and serological parameters in dengue patients- an analysis of 2022 cases - Dr. Anukampa Rai; Dr. Sheenam Azad; Dr. Sulekha Nautiyal; Dr. Seema Acharya (Tropical Journal of Pathology and Microbiology, 2019)
Background: Dengue is a mosquito borne viral disease in the world that has emerged as a major public health problem with its diverse clinical manifestations. Assessment of both the serological and hematological parameters are of importance for the diagnostic and prognostic utility.Aims: To study the various serological and hematological parameters in dengue patients and correlation between them.Materials and Methods: This was a prospective studyof 2022 seropositive dengue cases conducted in a Tertiary care hospital at Dehradun over a period of two years (September 2016-August 2018). Hematological analysis was done using SYSMEX XN1000 and various parameters (WBC, RBC and Platelet parameters) were evaluated. The subjects were divided into six serogroups (NS1 positive, NS1+IgM positive, IgM positive, IgG +NS1, IgM+IgG and triple positive) and correlation between different hematological and serological parameters was done using SPSS softwareand ANOVA test was used to calculate the p value.Results: A total of 2022 seropositive cases were studied out of which majority (72.3%) were NS1 positive. Male predominance was noted. Maximum cases were in the 11-20 year age group. The most affected parameters were platelet count (thrombocytopenia in 62.6%) and plateletcrit (reduced in 65.6%). There was a significant correlation of Hemoglobin. Platelet count, Plateletcrit, TLC, Percentage of neutrophil. lymphocyte and eosinophil amongst serological groups (p value was significant i.e. <0.05 in both the sex). In addition, RBC count also showed a significant association (p<0.05) in males.Conclusion: Peripheral blood parameters (esp RBC, Hb, Percentage of neutrophil. lymphocyte and eosinophil, platelet count and plateletcrit) along with serological markers are helpful in disease monitoring and predicting the disease course.